NUTRITION AS A BONES HEALTH FACTOR WITH SIGNIFICANT INFLUENCE - Rositsa Chamova; Maria Panteleeva; Eliyana Ivanova (Peytchinski Publishing, 2020)
Osteoporosis is a global health problem with increasing importance. It is a chronic, debilitating disease characterized by low bone density and deterioration of the micro architectonics of bone tissue. Although genetic factors largely determine the bone size and density, factors such as healthy eating, good physical activity and avoiding alcohol and smoking also play a key role. At all ages, healthy eating is an important factor in bone health. Aim: To study the eating habits that are important for bone health in women from Varna. Methods: A cross-sectional study of the eating habits of 139 women in Varna was conducted between January 2018 and March 2019. Questions, giving information on diet, frequency of consumption of certain food groups and beverages, affecting bone density, physical activity, demographic indicators are included in the questionnaire. Descriptive analysis of the data is done with SPSS version 19. Results: The average age of the participants was 29.86 ± 13.60 years. Daily consumption of milk and dairy products was found among 36.7% and 32.4% of the respondents respectively. The relative share of respondents who consume fish 1-2 times a week is 33.1%. The daily consumption of fruits and vegetables is 47.5% and 56.8% respectively. Conclusion: Nutrition plays an important role in reducing the risk of osteoporosis by affecting the development and maintenance of bone mass.